2018
DOI: 10.2174/1874285801812010071
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics Strains Modulate Gut Microbiota and Lipid Metabolism in Mule Ducks

Abstract: Background:Livestock production should respond to societal, environmental and economic changes. Since 2006 and the ban on antibiotics as growth factors in European Union, the use of probiotics has become widespread and has demonstrated the effect of intestinal microbiota on the performance of farm animals.Objective:The aim of this study was to investigate the effect of supplementation with Lactobacillus salivarius (as a probiotics strain or combined with other strains) on zootechnical performance, metabolic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 72 publications
(116 reference statements)
1
6
0
Order By: Relevance
“…Only 1% triton significantly increased LDH activity (*P < 0.05 versus control and probiotic groups) in the uptake of LCFA by small intestinal enterocytes [3]. The author reported that Lactobacillus plantarum LG42 could significantly decrease FAT/CD36 mRNA expression compared with untreated 3T3-L1 cells [25], but in our research, Ba failed to induce any effect on FAT/CD36 or PepT-1 expression, which is consistent with analyses by Even et al [26].…”
Section: Discussionsupporting
confidence: 91%
“…Only 1% triton significantly increased LDH activity (*P < 0.05 versus control and probiotic groups) in the uptake of LCFA by small intestinal enterocytes [3]. The author reported that Lactobacillus plantarum LG42 could significantly decrease FAT/CD36 mRNA expression compared with untreated 3T3-L1 cells [25], but in our research, Ba failed to induce any effect on FAT/CD36 or PepT-1 expression, which is consistent with analyses by Even et al [26].…”
Section: Discussionsupporting
confidence: 91%
“…It should be noted that the available information about the influence of probioticenriched feed on ducks' gut microbiota is inconclusive, as both beneficial [28] and neutral effects were reported earlier [45]. One of the reasons for such a discrepancy may be because two independent groups of birds, with and without probiotic supplementation, are usually compared: implementing the repeated measures design, i.e., sampling the same member of a group before and after the probiotic treatment, is more difficult in practice even in case of feces.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, Zhang et al proved that administration of Lactobacillus could change the diversity and composition of gut microbiota in weaned piglets [27]. On the other hand, some researchers studied the ability of probiotic strains to modulate the gut microbiota in mule ducks and found that probiotic treatment had no effect on gut microbial richness and diversity in either ileal and cecal samples initially, but at the end of the overfeeding period, both diversity and richness were decreased following probiotic treatment [28]. However, in the present study, addition of L. casei SY13 enhanced both parameters at both time points.…”
Section: Bacterial Diversity Of the Gut Microbiotamentioning
confidence: 99%